Heat stress on dairy productivity: Policy recommendations for the dairy value chain in Zambia - Notenbaert, An Maria Omer; Sikaceya, Noah (CGIAR Research Program on Livestock, 2021)
The dairy industry is a significant contributor to Zambia’s economy. In 2019, the country had over 3.6 million cattle, with a total milk output of 453 million litres and smallholder dairy producers accounting for over 72% of this. Zambian milk production is inadequate to satisfy the country’s expanding demand for dairy products. Climate-related heat stress is expected to exacerbate the problem. A recent study identified hotspot areas in Zambia where heat stress could have a negative impact on dairy productivity. Most of the country is having moderate heat stress conditions already and predictions point to the possibility of severe conditions in the future.